2007
DOI: 10.1007/s00392-007-0587-8
|View full text |Cite
|
Sign up to set email alerts
|

Are maximum P wave duration and P wave dispersion a marker of target organ damage in the hypertensive population?

Abstract: High blood pressure, LVH, diastolic dysfunction and increased left atrium diameter and volume shows parallelism in hypertensive cases. These physiopathological changes may cause different and heterogeneous atrial electrical conduction. This led to a marked increase in P(max) and PD in our cases. Thus, the results support the hypothesis that PD can be used as a non-invasive marker of target organ damage (LVH and LV diastolic dysfunction) in the hypertension population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 28 publications
2
41
2
Order By: Relevance
“…Studies have demonstrated a correlation between P-wave measurements, obtained through the conventional and/or high-resolution electrocardiogram, and the occurrence or recurrence of atrial fibrillation (after electrical cardioversion or radiofrequency ablation) 4-7 ; atrial arrhythmias in Brugada syndrome 8 , and after cardiac transplantation 9 ; hypertrophy and left diastolic dysfunction in hypertensive patients 10 ; HF 11,12 ; and improvement in ejection fraction after cardiac resynchronization therapy 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated a correlation between P-wave measurements, obtained through the conventional and/or high-resolution electrocardiogram, and the occurrence or recurrence of atrial fibrillation (after electrical cardioversion or radiofrequency ablation) 4-7 ; atrial arrhythmias in Brugada syndrome 8 , and after cardiac transplantation 9 ; hypertrophy and left diastolic dysfunction in hypertensive patients 10 ; HF 11,12 ; and improvement in ejection fraction after cardiac resynchronization therapy 13 .…”
Section: Introductionmentioning
confidence: 99%
“…In the classical model of myocardial ischemia cascade, angina symptoms are preceded by depolarization and repolarization changes on the electrocardiogram, which in turn are preceded by LV diastolic dysfunction from myocardial ischemia [24]. LV diastolic dysfunction results in the increase in the LV filling pressure, which subsequently may increase left atrial pressure and/or diameter [25].…”
Section: Discussionmentioning
confidence: 99%
“…Dagli et al [25] reported that resting PWD may be a good indicator for heart remodeling in hypertension as there is a correlation between high blood pressure, LV hypertrophy, diastolic dysfunction and increased volume of the left atrium. It was reported that P-wave morphology changes may result from left or right atrial hypertrophy and/or dilatation [26].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with uncontrolled hypertension had significantly prolonged P-wave duration and increased P-wave dispersion as compared to controls or controlled hypertension. 75,76 Likewise, patients with diabetes had significantly prolonged P-wave duration and increased P-wave dispersion as compared to normal controls. 77 Several studies showed that individuals with obesity had significantly prolonged P-wave duration and increased P-wave dispersion as compared with control groups.…”
Section: Atrial Conduction Delay and Afmentioning
confidence: 97%